Dual Hegemony in Islamic Education: A Critical Discourse Analysis of Gender Representations in Indonesian Islamic Textbooks - Kiki Ayu Hermawati; Agam Muhammad Rizki; Syifa Ulhusni; Purnomo; Wilhanul Haq; Mohammad Bachrul Falah (Nadwa: Jurnal Pendidikan Islam, 2026)
Islamic textbooks frequently function as vehicles for patriarchal ideology, embedding gender bias within religious pedagogy. This study examines gender representation in the Grade X, XI, and XII Akidah Akhlak textbooks under Indonesia's Merdeka Curriculum, analyzing how visual and narrative content construct asymmetrical religious authority. Using qualitative multimodal critical discourse analysis informed by Kress and van Leeuwen's visual grammar and Halliday's notion of narrative agency, the study codes all gender-identifiable illustrations (N=86) and narrative protagonists (N=52) across the three textbooks. Visually, males appear exclusively in 52.3% of images and females in 19.8%, while 27.9% depict both genders together, an exclusive male-to-female ratio of 2.6:1. Narratively, men are the central figure in 78.8% of stories compared with 21.2% for women, a ratio of 3.7:1; men are predominantly framed as religious authorities and historical agents, while women's narratives divide between exemplars of piety and figures associated with temptation, slander, or social vulnerability. These findings indicate a consistent, though not uniformly extreme, gender asymmetry across visual and textual modes, underscoring the need for more balanced representation in Islamic instructional materials.